Expandable neodymium-iron-boron sintered magnet and its manufacturing method and application
An expandable coating for neodymium iron boron sintered magnets addresses corrosion issues by forming a honeycomb structure upon heating, enhancing adhesion and wear resistance, thus improving motor assembly efficiency and durability.
Patent Information
- Application Number
- JP2023576226
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-11
- Filing Date
- 2022-06-13
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-06-13
AI Technical Summary
Neodymium iron boron sintered magnets are prone to corrosion in humid and high-temperature environments due to the chemical activity of the metallic Nd element, and conventional epoxy resin coatings provide insufficient hardness and wear resistance, leading to damage during motor assembly and packaging.
Application of an expandable coating with a thickness of 50-300 μm, composed of a water-soluble resin and thermoplastic expanded microspheres, which expands to form a honeycomb-like structure upon heating, providing enhanced adhesion and protection.
The expandable coating significantly improves the adhesion and wear resistance of neodymium iron boron sintered magnets, reducing assembly time and ensuring corrosion resistance, even in harsh conditions, while maintaining high bonding strength and hardness.
Smart Images

Figure 2022258069000001 
Figure 2022258069000002
Abstract
Description
[Technical field]
[0001] This application claims priority to a prior application, bearing patent application number 202110657206.1 and entitled "Expandable neodymium-iron-boron sintered magnet and its manufacturing method and application," filed with the State Intellectual Property Office of the People's Republic of China on June 11, 2021. The above prior application is hereby incorporated by reference in its entirety.
[0002] The present invention relates to the technical field of magnetic material surface protection, in particular to an expandable neodymium-iron-boron sintered magnet and its manufacturing method. By law Regarding. [Background technology]
[0003] Neodymium iron boron sintered magnets are known as the modern "King of Magnetism" due to their excellent residual magnetism, coercive force and magnetic energy product. They are therefore widely used in industries such as energy, transportation, machinery, medicine, IT and home appliances. In particular, with the development and use of new energy, the demand and application of Neodymium iron boron sintered magnets is expanding. The emergence of Neodymium iron boron sintered magnets has greatly promoted the development of permanent magnet motors, and products that use traditional ferrite magnets or samarium cobalt magnets in motor stators or rotors are being replaced with Neodymium iron boron sintered permanent magnets, reducing the weight of motors, improving the power coefficient and increasing output power. However, sintered Neodymium iron boron has a main phase of Nd2Fe 14 Among them, the chemical activity of metallic Nd is the strongest and it is highly susceptible to corrosion in wet, high-temperature and electrochemical environments, which significantly restricts the further expansion of the application fields of Nd-based sintered magnets.
[0004] At present, the electrical machinery industry generally uses electrophoretic epoxy resin coatings with a thickness of 15-30 μm for surface protection, which have strong bonding strength with the substrate and excellent advantages such as acid resistance and base resistance. However, in the assembly process of the motor, it is necessary to use potting resin adhesive for assembly, that is, the magnet is inserted into the magnetic steel groove, and then the resin adhesive is injected and heated to harden the magnet in the magnetic steel groove. Therefore, in the assembly process of the motor, not only do it need to consider factors such as the fluidity, adhesion, thermal conductivity, oil resistance, and environmental protection of the resin adhesive, but at the same time, since the heat hardening of the resin adhesive takes a relatively long time, it usually needs to be heated and hardened for more than 24 hours to meet the adhesive strength requirements in the assembly of the motor. In addition, although the epoxy resin adhesive coating has excellent performance, the hardness of the coating is relatively small and the wear resistance is very poor, making it easy to break during packaging and transportation and motor assembly, and since the epoxy resin adhesive coating is a cathodic protective coating, once the coating is broken, the magnet will be severely corroded. Therefore, how to fix the magnet in the magnetic steel groove and increase the hardness and wear resistance of the coating is a technical problem to be solved in the art. Summary of the Invention [Means for solving the problem]
[0005] In order to improve the above technical problems, the present invention provides an expandable NdFeB-based sintered magnet, including a NdFeB-based sintered magnet and an expandable coating applied to the surface of the NdFeB-based sintered magnet.
[0006] According to an embodiment of the present invention, the thickness of the expandable coating is 50-300 μm, preferably 80-150 μm, illustratively 50 μm, 80 μm, 110 μm, 150 μm, 180 μm, 200 μm, 250 μm, 300 μm.
[0007] According to an embodiment of the present invention, the expandable coating is softened at 60-100°C, illustratively at 60°C, 70°C, 80°C, 90°C, or 100°C.
[0008] According to an embodiment of the present invention, in the absence of pressure, the thickness expansion rate of the expandable coating is 200-400%, preferably 300-400%, illustratively 200%, 220%, 250%, 280%, 300%, 350%, 400%.
[0009] The expandable coating of the present invention is heated to 165-210°C, whereby the organic resin inside the expandable coating is crosslinked to achieve a fixed shape.
[0010] According to an embodiment of the invention, the expandable coating exhibits a honeycomb-like coating after expansion. Preferably, the expandable coating exhibits essentially the morphology shown in FIG.
[0011] In the present invention, the expansion ratio = thickness of the coating after expansion in the free state / thickness of the expandable coating before expansion.
[0012] According to an embodiment of the present invention, the expandable coating includes at least a water-soluble resin and a foaming agent.
[0013] The water-soluble resin is preferably at least one selected from a water-soluble acrylic resin, a water-soluble epoxy resin, and a water-soluble urethane resin, and is preferably selected from a water-soluble acrylic resin.
[0014] According to an embodiment of the present invention, in the expandable coating, the solid content of the water-soluble resin is 30-50%, illustratively 30%, 35%, 40%, 50%.
[0015] Preferably, the foaming agent is a thermoplastic expanded microsphere, and the diameter of the thermoplastic expanded microsphere is preferably 5 to 30 μm, preferably 5 to 20 μm, illustratively 5 μm, 8 μm, 10 μm, 12 μm, 16 μm, 18 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 120 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 15 μm, 18 μm, 20 μm, 25 μm, and 30 μm.
[0016] According to an embodiment of the present invention, after the expandable coating is expanded, the area of the expanded microspheres occupies 60-90% of the cross-sectional area of the expandable coating, illustratively 60%, 70%, 80%, 90%.
[0017] According to an embodiment of the present invention, at temperatures between 110 and 210° C. (eg, 110° C., 120° C., 130° C., 140° C., 150° C., and 160° C.), the expandable microspheres within the expandable coating expand stepwise.
[0018] Preferably, the average diameter of the thermoplastic expanded microspheres is 10 to 15 μm, illustratively 10 μm, 12 μm, μm, 15 μm.
[0019] The expansion temperature of the thermoplastic expandable microspheres is preferably 110 to 210°C, for example, 110°C, 120°C, 150°C, 160°C, 170°C, 180°C, or 200°C.
[0020] The maximum heat-resistant temperature of the thermoplastic expanded microspheres is preferably 145 to 235°C, e.g., 145°C, 160°C, 180°C, 200°C, 215°C, or 235°C.
[0021] According to an embodiment of the present invention, the expandable coating is produced by applying an expandable paint comprising at least a composition of a water-soluble resin and a blowing agent.
[0022] According to an embodiment of the present invention, the weight percentage of the water-soluble resin in the expandable coating is 45-65%, for example 50-60%.
[0023] According to an embodiment of the present invention, the weight percentage of the foaming agent in said expandable coating is 10-30%, such as 15-25%.
[0024] According to an embodiment of the present invention, the expandable paint optionally comprises Hectorite For example, the above Hectorite The weight percentage of is 0.1 to 0.5%, for example 0.2 to 0.4%.
[0025] According to an embodiment of the present invention, the expandable coating optionally further comprises dipropylene glycol butyl ether, for example, the weight percentage of the dipropylene glycol butyl ether is 0.5-3%, such as 0.8-2.5%.
[0026] According to an embodiment of the present invention, the expandable coating optionally further comprises propylene glycol, for example, the weight percentage of the propylene glycol is 1-3%, such as 1.5-2.5%.
[0027] According to an embodiment of the present invention, the expandable coating material optionally further comprises an acrylic thickener, for example, the weight percentage of the acrylic thickener is 0.2-0.8%, such as 0.3-0.6%.
[0028] According to an embodiment of the present invention, the expandable coating material optionally further comprises a dispersant, for example, the weight percentage of the dispersant is 0.1-0.5%, such as 0.2-0.4%. Preferably, the dispersant is ethylene glycol, sodium oleate, carboxylate, and the like.
[0029] According to an embodiment of the present invention, the expandable coating optionally further comprises a leveling agent, for example, the weight percentage of the leveling agent is 0.1-0.5%, such as 0.2-0.4%.
[0030] Preferably, the leveling agent is a silicone oil, an organosiloxane, or the like. According to an embodiment of the present invention, the expandable paint further comprises water. According to an embodiment of the present invention, the sum of the weight percentages of each component in the expandable coating is 100%.
[0031] According to an embodiment of the present invention, a method for producing the expandable paint comprises mixing the components to obtain the expandable paint.
[0032] Preferably, the method for producing the expandable coating material further comprises dispersing the mixed components in water to obtain a dispersion, and further comprises stirring the dispersion to uniformly mix the components. In the present invention, the expanded microspheres are screened by a screener to select those having a particle size in the range of 5-30 μm, which are then mixed with a water-soluble resin and stirred at room temperature for 30-60 minutes.
[0033] According to an embodiment of the present invention, the expandable coating comprises 45-65% water-soluble resin, 10-30% foaming agent, Hectorite It is produced by applying an expandable paint containing the following weight percentage composition: 0.1-0.5% polypropylene glycol, 0.5-3% dipropylene glycol butyl ether, 1-3% propylene glycol, 0.2-0.8% acrylic thickener, 0.1-0.5% dispersant, and 0.1-0.5% leveling agent.
[0034] The inventors of the present invention have surprisingly found that in the thermal expansion process, the expansion rate needs to be controlled within the range of 300-400%, and if the expansion rate is less than 200%, the gap between the magnet and the magnetic steel groove cannot be densely filled, while if the expansion rate is more than 400%, the bridges inside the coating will be destroyed and the pressing force will be insufficient. The expansion rate is related to conditions such as the content of microspheres in the coating, particle size, expansion temperature, expansion time, and coating thickness, and the present invention can control the expansion ratio within an appropriate range by optimizing the amount of raw materials of each composition and the expansion conditions in the expandable coating, thereby producing a neodymium-iron-boron sintered magnet with even better adhesive pressing force.
[0035] According to an embodiment of the present invention, the neodymium-iron-boron based sintered magnet has a main phase of NdFe 14 It consists of B, Nd-rich phase and B-rich phase.
[0036] The present invention further provides a method for producing the above-mentioned expandable sintered magnet, which includes applying the expandable paint of each of the above-mentioned compositions to a surface of a neodymium-iron-boron sintered magnet, and producing the above-mentioned expandable sintered magnet through a preliminary curing treatment.
[0037] According to an embodiment of the present invention, the method further includes a step of surface pretreatment before applying the expandable paint to the NdFeB sintered magnet.
[0038] According to one embodiment of the present invention, the above surface pretreatment includes the processes of chemical and ultrasonic degreasing, pickling and water rinsing for the surface of the NdFeB sintered magnet. Preferably, the oil removal liquid used in the oil removal process is a combined solution of base and surfactant.
[0039] Preferably, the base is sodium hydroxide or sodium carbonate, and the concentration is 10 to 20 g / L, for example, 10 g / L, 15 g / L, or 20 g / L.
[0040] Preferably, the surfactant is sodium dodecyl sulfonate or sodium dodecyl sulfate, and the concentration is 2 to 6 g / L, for example, 2 g / L, 3 g / L, 4 g / L, 5 g / L, or 6 g / L.
[0041] Preferably, the temperature of the oil removal liquid is 30 to 70° C., e.g., 30° C., 40° C., 50° C., 60° C., or 70° C. Furthermore, the oil removal time is 1 to 20 min, e.g., 1 min, 5 min, 10 min, 15 min, or 20 min.
[0042] Preferably, the acid used in the pickling may be an aqueous solution of nitric acid or citric acid.
[0043] Preferably, the acid concentration used in the pickling is 5 to 30 wt%, e.g., 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, or 30 wt%, and the pickling time is 5 to 30 s, e.g., 5 s, 10 s, 15 s, 20 s, 25 s, or 30 s.
[0044] Preferably, the water washing includes ultrasonic water washing using pure water, and the time for the water washing is 20 to 120 s, e.g., 20 s, 30 s, 50 s, 80 s, 100 s, or 120 s.
[0045] According to an embodiment of the present invention, the application method includes, but is not limited to, spraying, printing, dipping, smearing, etc., preferably spraying.
[0046] According to an embodiment of the present invention, the thickness of the coating is 50 to 300 μm, preferably 80 to 150 μm, and illustratively 50 μm, 80 μm, 110 μm, 150 μm, 180 μm, 200 μm, 250 μm, and 300 μm.
[0047] The inventors of the present invention have surprisingly found that if the coating thickness of the expandable coating is too thin, the expansion force during the assembly process is insufficient, and therefore the desired pressing force cannot be achieved. However, if the coating thickness of the expandable coating is too thick, the surface of the coating is prone to falling off and cracking. In addition, the coating thickness of the expandable coating is related to the preliminary dimension of the magnetic steel groove, and the larger the preliminary dimension, the thicker the coating thickness required. The inventors have surprisingly found that after the coating expands, the expansion and compression rate of the coating in the magnetic steel groove is most effective when it is between 35% and 65%, at which time the adhesion force between the magnet and the magnetic steel groove is the strongest, and the pressing force of the magnet in the magnetic steel groove is the strongest.
[0048] Expansion / compression ratio m=(H1-H0) / (H2-H0) Wherein, H0 is the applied thickness of the expandable coating, H1 is the expanded thickness of the expandable coating in the magnetic steel groove, and H2 is the expanded thickness of the expandable coating in the natural state.
[0049] According to an embodiment of the present invention, the pre-curing treatment may be to naturally dry the coating at room temperature (15 to 35°C) or to dry the coating at a medium to low temperature (35 to 90°C) baking condition to form a complete coating.
[0050] The present invention further provides the application of the above expandable NdFeB based sintered magnet in motor rotors.
[0051] The present invention further provides a motor rotor workpiece, comprising the expandable neodymium-iron-boron-based sintered magnet.
[0052] The present invention further provides a method for assembling the motor rotor workpiece, including assembling the expandable NdFeB sintered magnet into a magnetic steel groove, and undergoing a heating and expanding process to manufacture the motor rotor workpiece.
[0053] The present inventors have surprisingly found that the final use performance of the intumescent coating is related to the expansion temperature, heating rate, and warming time during the expansion assembly process, and that the expansion temperature directly affects the final structure of the intumescent coating.
[0054] According to an embodiment of the present invention, the above-mentioned thermal expansion treatment adopts a two-stage heating method, and the expansion temperature in the first expansion stage is 110-160° C., e.g., 110° C., 120° C., 130° C., 140° C., 150° C., and 160° C. Furthermore, the heating rate in the first expansion stage is 5-15° C. / min, e.g., 5° C. / min, 10° C. / min, and 15° C. / min.
[0055] If the expansion temperature in the first expansion stage is lower than 110℃, a large amount of microspheres cannot expand and the required expansion ratio cannot be reached. However, if the expansion temperature in the first expansion stage is higher than 160℃, the microspheres will expand rapidly, but due to the different particle sizes of the microspheres in the coating, the microspheres with small particle sizes will expand rapidly and burst, causing the coating to collapse early, and therefore the corresponding supporting force cannot be obtained. In addition, if the heating rate in the first expansion stage is controlled to 5-15℃ / min, the expanded coating can be expanded uniformly, and the liquefied hydrocarbons in the expanded microspheres can be fully vaporized during the heating process, so that the coating can be expanded gradually and uniformly.
[0056] According to an embodiment of the present invention, the expansion temperature in the second expansion stage of the thermal expansion treatment is 180-210°C, e.g., 180°C, 190°C, 200°C, or 210°C. Furthermore, the temperature rise rate in the second expansion stage is 30-60°C / min, e.g., 30°C / min, 40°C / min, 50°C / min, or 60°C / min. After the coating is uniformly expanded, the temperature rise is accelerated to rapidly harden the thermoplastic resin in the coating.
[0057] The thermoplastic expanded microspheres of the present invention are composed of a thermoplastic resin shell and a propellant enclosed therein, and 70% or more of the propellant is isooctane. In addition to isooctane, the propellant may be selected from other liquids within a suitable boiling point range, such as butane, pentane, heptane, etc. In the heat-expansion process, after the liquid propellant in the expanded microspheres reaches its boiling point, the propellant evaporates, increasing the internal pressure of the microspheres and causing a volume change in the propellant, which deforms and expands the shell that has become soft due to heat, while softening the shell to restrict the expansion of the microspheres. The temperature at the start of expansion is Tstar, and the temperature at which the maximum expansion degree is reached is T max and the temperature is T max Above this threshold, the propellant is released through the thermoplastic shell to the point where the microspheres begin to rupture.
[0058] In the first expansion stage, the high boiling point solvent in the coating volatilizes, dissolving the shell of the expanded microspheres with a particle size of <10 μm and a wall thickness of <3 μm, thinning the shell wall, and bursting when the maximum expansion temperature is not reached. >60% of the microspheres in the expansion coating burst, and after bursting, the propellant in the microspheres is released, the microspheres do not accelerate the expansion and form a void structure, and the thermoplastic resin on the outer wall of the microspheres crosslinks with the water-soluble resin in the coating to form a network structure, which increases the adhesion force in the magnetic steel groove of the magnet.
[0059] In the second expansion stage, the expanded microspheres with a particle size of >10 μm in the coating continue to expand, but in this case, the high boiling point solvent in the coating has already volatilized and does not accelerate the rupture of the shell of the expanded microspheres. In this case, the maximum expansion temperature in the second expansion stage is lower than that of the microspheres with a particle size of >10 μm, and the release rate of the propellant becomes slow.
[0060] The expanding microspheres of the present invention contain 70% or more isooctane as a releasing agent. By detecting the amount of isooctane released during the expansion process, the expansion rate of the coating can be controlled so that 60% or more of the microspheres in the coating can be burst, and then crosslinked with the water-soluble resin to form a network structure.
[0061] The present invention can control the rate of bursting of the expanded microspheres by detecting the collected gas and determining the amount of isooctane released during the expansion process. The detection method is as follows: A magnet (35.5 mm x 16.5 mm x 5.5 mm) coated with the expansion coating is taken and placed in a sealed sample bottle. It is heated at the same heating temperature and heating rate as the expansion process conditions during the expansion assembly process. After heating, it is naturally cooled to 60°C, and the gas in the sample bottle is purged into a gas phase column using nitrogen gas and measured. The isooctane content w1 at that time is recorded. The magnet in the sample bottle is continuously heated to the maximum expansion temperature T max Heat at a higher temperature (240° C.) for 3 h until the microspheres in the intumescent coating are completely ruptured and the isooctane in the microspheres is completely released, and the isooctane content w2 at that time is recorded.
[0062] From the amount of isooctane released, the burst ratio of the microspheres, q=w1 / (w1+w2), is calculated.
[0063] After extensive experimentation, the inventors surprisingly found that when the microsphere burst ratio q is within the range of 60-85%, all of the expandable coatings exhibit excellent support effect, all of the expandable magnets have a relatively high pressing force in the usage environment, and the coating has the highest adhesion.
[0064] The expansion coating first undergoes a softening process, during which the expansion microspheres in the coating expand in volume due to heat, increasing the overall thickness of the expansion coating and exerting a pressing force on the inner wall of the motor assembly; at the same time, the heat-melting resin in the expansion coating exerts a certain adhesive force after softening, thereby fixing the sintered magnet to the motor assembly and completing the assembly process. Effect of the Invention
[0065] (1) Instead of applying a potting resin adhesive to a conventional epoxy resin adhesive coated magnet, the present invention uses a neodymium iron boron based sintered magnet coated with an expandable coating, and inserts the magnet coated with the expandable coating into a magnetic steel groove, and fixes the magnet in the magnetic steel groove by utilizing the irreversible expansion of the coating itself. At the same time, the use of the expandable coating of the present invention significantly shortens the motor assembly time and improves the motor assembly accuracy. In addition, the sintered magnet coated with the expandable coating of the present invention has excellent properties such as excellent high temperature resistance, anti-aging, corrosion resistance and high bonding strength.
[0066] (2) The present invention utilizes a specially formulated, environmentally friendly water-based intumescent coating instead of traditional potting resins, thereby reducing VOC emissions and environmental issues caused by solvent-based binders.
[0067] (3) The present invention controls the content of expandable microspheres in the expandable coating to 10-30%, so that after expansion by heat, the water-soluble resin crosslinks with the expandable microspheres to form a honeycomb-like porous structure, in which the porosity reaches 60-90%, and the adhesive pressing force of the assembly at room temperature is 1000 N / cm 2 Greater than.
[0068] (4) The expandable coating produced by the present invention has a hardness equal to or greater than Mitsubishi Pencil H at room temperature (25°C), has high abrasion resistance, and is not easily damaged during transportation. In addition, even if the expandable coating of the present invention is immersed in 10% hydrochloric acid or 10% sodium hydroxide solution for 24 hours or more, the coating does not suffer from defects such as softening, dissolution, or falling off, and therefore exhibits relatively high acid resistance and base resistance. At the same time, even if the coating is immersed in 170°C engine oil for 500 hours or more, the coating still does not suffer from problems such as softening, swelling, or falling off, and therefore exhibits relatively high heat oil resistance. [Brief description of the drawings]
[0069] [Figure 1] 1 is an electron microscope photograph (magnified 300 times) of the expandable coating prepared in Example 1 after expansion. [Diagram 2] 1 is an electron microscope photograph (magnified 250 times) of the expandable coating (Sample 5) produced in Example 5 after expansion. [Diagram 3] 1 is an electron microscope photograph (magnified 250 times) of the expandable coating (Sample 6) prepared in Example 6 after expansion. [Figure 4] 1 is an electron microscope photograph (magnified 500 times) of the expandable coating (Sample 10) prepared in Example 10 after expansion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0070] The technical solution of the present invention will be described in more detail below with reference to specific examples. It should be understood that the following examples are merely illustrative and interpretive of the present invention and should not be interpreted as limiting the scope of the claims of the present invention. Any technology realized based on the above content of the present invention is included in the scope of the claims of the present invention.
[0071] Unless otherwise specified, all materials and reagents used in the following examples are commercially available or can be prepared by known methods. Example 1 In this example, a neodymium iron boron sintered magnet (unmagnetized) with dimensions of 35.5 mm×16.5 mm×5.5 mm was used, and the dimensions of the magnetic steel groove with the assembled motor rotor were 36 mm×17 mm×6 mm.
[0072] Magnet surface pretreatment: Using a composite oil removal solution with a sodium hydroxide concentration of 15 g / L and a sodium dodecylsulfonate concentration of 3 g / L, the neodymium iron boron sintered magnet was subjected to oil removal for 2 min at 60°C, then pickled with a 25 wt% citric acid aqueous solution for 15 s, and finally the neodymium iron boron sintered magnet was ultrasonically washed with deionized water for 2 min.
[0073] The preparation of expandable paint: 55% water-soluble acrylic resin, 30% water, 10% foaming agent, Hectorite The expandable paint was prepared with the following composition (calculated by weight percentage): 0.2%, dipropylene glycol butyl ether 1.5%, propylene glycol 2%, acrylic thickener 0.5%, ethylene glycol 0.4%, and polydimethylsiloxane 0.4%. The blowing agent was selected to be thermoplastic expandable microspheres with an average diameter of 13 μm.
[0074] Coating process: The above expandable paint was applied to the magnet surface by compressed air spraying at a spray speed of 120 mm / s, coating thickness of 110 μm, nozzle-to-workpiece distance of 15 cm, spray gun-to-workpiece angle of 25°, and argon gas pressure of the spray gun of 0.6 MPa.
[0075] Pre-curing treatment: The magnet surface coated with the expandable paint was heated to 50°C for pre-curing treatment to obtain a coating with a thickness of 110 μm.
[0076] Coating expansion: In the absence of pressure, the magnet coated with the expansion coating was placed in a high-temperature drying box, and the magnet was heated to 120°C in two stages, first at 120°C and kept at 4°C for 5 min, and then rapidly heated to 170°C and kept at 4°C for 3 min. The heating rate of the first stage was 5°C / min, and the heating rate of the second stage was 50°C / min. With the increase in temperature, the gas pressure inside the shell of the expansion microsphere increased, the thermoplastic shell softened, and the expansion volume of the microsphere increased significantly. At this time, the resin inside the expansion coating softened, and the thickness of the expansion coating increased with the increase in the volume of the expansion microsphere. As shown in Figure 1, the microspheres expanded uniformly, and the microsphere walls and the resin cross-linked with each other to form a stable support structure. The expansion coating was composed of water-soluble acrylic resin and expansion microspheres. The thickness of the expansion coating expanded from 110 μm after the pre-curing treatment to 394 μm, and the expansion rate reached 358%. After expansion, the expanded coating had a honeycomb shape, and the cross-sectional area of the expanded microspheres accounted for 82% of the cross-sectional area of the expanded coating. (In the present invention, the ratio of the cross-sectional area of the expanded microspheres to the cross-sectional area of the expanded coating in one cross section was calculated by first taking a scanning electron microscope photograph of the cross section of the expanded coating after expansion, then recognizing the gaps in the cross section from the image, calculating the sum of the gap areas, and using the gap area as the ratio of the cross-sectional area of the expanded microspheres to the cross-sectional area of the expanded coating.)
[0077] The magnet coated with the expansion coating was assembled into the magnetic steel groove of the motor rotor and placed in a high-temperature drying box, which was heated to 120°C in two stages, kept at 120°C for 5 min, and then rapidly heated to 170°C for 3 min, with the heating rate of 5°C / min in the first stage and 50°C / min in the second stage. (The magnet was assembled into the magnetic steel groove, and the expandable coating expanded due to heat, pressing against the inner wall of the magnetic steel groove and filling the gap between the magnetic steel groove and the magnet. At the same time, the resin inside the coating and the expandable microspheres were bridged to form a honeycomb-like coating structure. Due to the restriction of the inner wall of the magnetic steel groove, the coating could not expand to its maximum during the expansion process, so that the honeycomb-like structure was compressed and wrinkled after expansion.) After heating was completed, the motor rotor was cooled under natural conditions. Due to the change in environmental temperature, the volume of the expandable microspheres increased, and the change was irreversible, so that the volume of the coating increased, filling the gap between the magnet and the inner wall of the magnetic steel groove and tightly fixing the magnet inside the magnetic steel. The magnet product obtained at this time was named Sample 1.
[0078] In this state, the adhesive pressing force of the magnet at room temperature and at high temperature was measured, and the adhesive pressing force at room temperature (25°C) was 1200 N / cm 2 , adhesive pressing force at high temperature (170℃) is 530 N / cm 2 It was. [Examples 2 to 5] The surface pretreatment method, expandable paint, and coating process were the same as those in Example 1. A magnet with an expandable coating thickness of 110 μm was inserted into the magnetic steel groove. Different first expansion temperatures, second expansion stage expansion temperatures, heating rates, and expansion times were used to obtain the optimal assembly process conditions, and the results are shown in Table 1 below.
[0079] [Table 1]
[0080] As can be seen from the results in Table 1, the pressing force at room temperature and the pressing force at high temperature are correlated with the expansion temperature and the heating rate, and the optimal assembly process conditions could be obtained through optimization.
[0081] At the same time, the amount of isooctane released was measured to estimate the burst rate of the microspheres. It was found that the burst rate was between 60% and 85%, and that the burst microspheres bridged with the resin coating. The resulting coating had a stable structure and could stably support the gap between the magnet and the magnetic steel groove.
[0082] FIG. 1 shows the coating state of Sample 1 after expansion. As can be seen from the figure, the microspheres expanded uniformly, and the microsphere walls and the resin cross-linked with each other to form a stable support structure.
[0083] FIG. 2 shows the coating state of Sample 5 after expansion. As can be seen from the figure, many microspheres burst and there were large gaps between the microspheres due to fusion, so the adhesive strength of the coating at high temperatures was relatively low. Example 6 In this example, a neodymium iron boron sintered magnet (unmagnetized) with dimensions of 35.5 mm×16.5 mm×5.5 mm was used, and the dimensions of the magnetic steel groove with the assembled motor rotor were 36 mm×17 mm×6 mm.
[0084] Using the same surface pretreatment as in Example 1, a composite oil removal solution with a sodium hydroxide concentration of 15 g / L and a sodium dodecylsulfonate concentration of 3 g / L was used to remove oil from the neodymium iron boron sintered magnet at 60°C for 2 minutes, followed by pickling for 15 seconds using a 25 wt% aqueous citric acid solution. Finally, the neodymium iron boron sintered magnet was ultrasonically washed in deionized water for 2 minutes.
[0085] The expandable powder coating material from AKZO-Nobel was selected, which consists of 50% epoxy resin powder, 20% hardener, 10% elastomer resin, and 20% thermoplastic expandable microspheres. The expandable coating material was applied to the magnet surface by compressed air spraying at a spray speed of 60 mm / s, a coating thickness of 110 μm, a nozzle-to-workpiece distance of 10 cm, an angle between the spray gun and the workpiece of 25°, and an argon gas pressure of the spray gun of 0.6 MPa.
[0086] The magnet coated with the expansion coating was assembled in the magnetic steel groove of the motor rotor, placed in a high-temperature drying box, and heated at 190°C for 20 min. The thermoplastic expansion microspheres expand in volume with temperature changes, so the entire coating expands and the epoxy resin hardens at the same time, so the coating is stable and does not shrink. The cross-sectional structure of the expansion coating was observed with an electron microscope, and as shown in Figure 3, the thickness of the expansion coating was 110 mm after the pre-curing treatment. The microspheres expanded from 1.5 μm to 180 μm, with an expansion rate of 163%. They were also clearly visible after expansion. The edges of the thermoplastic expanded microspheres were clearly visible, and when the expanded microspheres were heated, the volume of the microspheres increased only due to the vaporization of the liquid alkane inside the microspheres. The amount of isooctane released from the expanded microspheres was measured to infer whether the microspheres in the coating would burst. As can be seen from the measurement, when heated at 190°C for 20 min, the amount of isooctane released w1 was 1.52 mg / L. When heated to 240°C and held for 3 h to completely burst the expanded microspheres in the coating, the amount of isooctane released w2 was 5.34 mg / L. By calculating the formula, the burst rate of the expanded microspheres in the actual assembly process could be estimated as q=w1 / (w1+w2)=1.52 / (1.52+5.34)=22%.
[0087] As can be seen from FIG. 3, the cross-sectional area of the expanded microspheres accounted for 35% of the expanded coating. In this state, the adhesive pressing force of the magnet at room temperature and at high temperature was measured, and the adhesive pressing force at room temperature (25°C) was 920 N / cm 2, adhesive pressing force at high temperature (170℃) is 310 N / cm 2 It was. [Examples 7 to 14] In this example, a neodymium iron boron sintered magnet (unmagnetized) with dimensions of 35.5 mm×16.5 mm×5.5 mm was used, and the dimensions of the magnetic steel groove with the assembled motor rotor were 36 mm×17 mm×6 mm.
[0088] Using the same surface pretreatment process and expandable paint as in Example 1, the expandable paint was applied to the magnet surface by compressed air spraying to a spray thickness of 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, and 150 μm, respectively.
[0089] The magnet coated with the expansion coating was assembled into the magnetic steel groove of a motor rotor, then placed in a high-temperature drying box and heated in two stages: first to 120°C and kept at that temperature for 5 minutes, then rapidly heated to 170°C and kept at that temperature for 3 minutes, during which the heating rate in the first stage was 5°C / min, and in the second stage was 50°C / min. The pressing force of the magnet at room temperature and at high temperature in the operating state was measured, and the results are shown in Table 2 below.
[0090] Expansion rate = H2 / H0 Compression ratio = (H1-H0) / (H2-H0) Wherein, H0 is the coating thickness, H1 is the expanded thickness of the expandable coating in the magnetic steel groove, and H2 is the expanded thickness of the expandable coating in the natural state.
[0091] [Table 2]
[0092] FIG. 4 shows the coating state of sample 10 in the magnetic steel groove. As can be seen from FIG. 4, the coating is restricted by the inner wall of the magnetic steel groove during the expansion process, so the expansion coating is compressed and wrinkled.
[0093] When the expandable coating is compressed strongly, a relatively large stress is generated at the contact surface of the expandable coating and the contact surface between the inner wall of the magnetic steel groove, the stress per unit area of the coating increases, the internal defects of the coating increase exponentially, and the cohesive strength of the adhesive layer decreases. Therefore, by controlling the compression rate to 35% or more, it is possible to manufacture a magnet with relatively good pressing force at room temperature and high temperature.
[0094] The higher the compression ratio, the more economically advantageous it is. After extensive experimentation, the inventors surprisingly found that when the compression ratio is greater than 65%, the coating becomes sensitive to shrinkage stress and thermal stress due to temperature changes, which leads to a loss of cohesive strength of the magnet, thereby reducing the pressing force of the magnet at room temperature and at high temperatures.
[0095] The above describes the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modifications, equivalent replacements, improvements, etc. made within the scope of the spirit and principles of the present invention are included within the scope of the claims of the present invention.
Claims
1. A method for producing an expandable neodymium-iron-boron based sintered magnet, comprising the steps of: The manufacturing method includes applying an expandable paint to a surface of a neodymium-iron-boron based sintered magnet, and manufacturing the expandable neodymium-iron-boron based sintered magnet through a preliminary curing process; The expandable coating composition includes, by weight percentage, 45-65% water-soluble resin, 10-30% foaming agent, 0.1-0.5% hectorite, 0.5-3% dipropylene glycol butyl ether, 1-3% propylene glycol, 0.2-0.8% acrylic thickener, 0.1-0.5% dispersant, and 0.1-0.5% leveling agent, and the solid content of the water-soluble resin is 30-50%; the blowing agent is a thermoplastic expanded microsphere, the thermoplastic expanded microsphere comprising a thermoplastic resin shell and a propellant encapsulated therein, 70% or more of the propellant being isooctane, butane, pentane, or heptane, and the thermoplastic expanded microsphere has a diameter of 5 to 30 μm; The expandable NdFeB sintered magnet includes a NdFeB sintered magnet and an expandable coating applied to a surface of the NdFeB sintered magnet, the expandable coating being manufactured by applying the expandable paint; the thickness of said expandable coating is between 50 and 300 μm; When the thermal expansion treatment is performed in the absence of pressure and at a temperature of 110-210°C, the thickness expansion rate of the expandable coating is 200-400%; The heat expansion treatment adopts a two-stage heating method, the expansion temperature of the first expansion stage is 110-160°C, the heating rate of the first expansion stage is 5-15°C / min, the expansion temperature of the second expansion stage of the heat expansion treatment is 180-210°C, the heating rate of the second expansion stage is 30-60°C / min; After the expandable coating is expanded, the area of the expanded microspheres occupies 60-90% of the cross-sectional area of the expandable coating.
2. The method for producing an expandable neodymium-iron-boron sintered magnet according to claim 1 .
2. The water-soluble resin is at least one selected from a water-soluble acrylic resin, a water-soluble epoxy resin, and a water-soluble urethane resin.
2. The method according to claim 1 .
3. The average diameter of the thermoplastic expanded microspheres is 10 to 15 μm.
2. The method according to claim 1 .
4. The weight percentage of the water-soluble resin in the expandable coating is 50 to 60%, and The weight percentage of the blowing agent in the expandable coating is 15-25%; 2. The method according to claim 1 .
5. The dispersant is ethylene glycol, sodium oleate, or a carboxylate; The leveling agent is a silicone oil or an organosiloxane.
2. The method according to claim 1 .
6. The neodymium-iron-boron sintered magnet has a main phase Nd 2 Fe 14 B, Nd-rich phase and B-rich phase 2. The method according to claim 1 .
7. Before applying the expandable paint to the neodymium iron boron based sintered magnet, the method further includes a step of surface pretreatment, The surface pretreatment includes the processes of chemical and ultrasonic degreasing, pickling, and water washing on the surface of the NdFeB sintered magnet.
2. The method according to claim 1 .
8. An expandable neodymium-iron-boron sintered magnet obtained by the manufacturing method according to claim 1.
9. The expandable neodymium-iron-boron sintered magnet according to claim 8, The expandable neodymium-iron-boron sintered magnet is assembled into a magnetic steel groove and undergoes a heating and expansion treatment; 4. A motor rotor workpiece characterized by:
10. The method includes assembling the expandable NdFeB sintered magnet according to claim 8 into a magnetic steel groove, and then carrying out a thermal expansion process to manufacture the motor rotor workpiece; The heat expansion treatment adopts a two-stage heating method, the expansion temperature of the first expansion stage is 110-160°C, and the heating rate of the first expansion stage is 5-15°C / min; The expansion temperature of the second expansion stage of the thermal expansion treatment is 180-210°C, and the heating rate of the second expansion stage is 30-60°C / min; 10. The method for assembling a motor rotor workpiece according to claim 9, further comprising the steps of:
